Preliminary estimation of the efficacy of Fusarium sporotrichioides Sherb. as biological control agent against common milkweed (Asclepias syriaca L.) - Tóth, Tamás; Szilágyi, Arnold; Kövics, György (Acta Agraria Debreceniensis, 2018)
A study of fungi responsible for severe leaf spots of common milkweed (Asclepias syriaca L.) in the Hajdúság region (East Hungary), Fusarium sporotrichioides and Alternaria alternata were isolated from infested leaf tissues. F. sporotrichioides was the most virulent fungus in pathogenicity tests conducted on healthy leaves of common milkweed plants. Inoculation of common milkweed (A. syriaca) in different growth stages with F. sporotrichioides yielded similar symptoms as the original ones. Spray mixtures containing 1.0×106 conidia/ml gave effective control when common milkweed plants were sprayed until runoff occurred. Laboratory (wet chamber) and field experiments showed that asexual spores of the fungal pathogen, F. sporotrichioides, exhibited bioherbicidal activity against common milkweed (A. syriaca).More efficient control efficacy was observable on elder plants (at flowering stage) than younger ones. These results initiate that this fungus may be a biocontrol agent for controlling this invasive weed but should clarify its hosts because it could infect cultivated plants as well.